THE CONCEPT OF FORMING ISLAMIC MORALS IN EARLY CHILDHOOD - Hana Rizayanti; Risal Fratama; Sri Nurhidayah (Proceeding International Seminar of Islamic Studies, 2023)
The development of religion and morality in early childhood is the foundation for guidance and direction. However, the facts show that there are still many parents and educators who still need information about knowledge regarding how to form Islamic morals in early childhood. Therefore, an in-depth study is needed to find concepts to shape religious character in early childhood. This study aims to examine the concept of moral formation in early childhood with the perspective of Islamic educational values. The type of research method used is literature. The results of this study are to find four that form the basis of the concept of forming Islamic morals in early childhood. First, providing guidance in a positive direction. Second, set an example of good behavior and ethics. Third, the habit of doing good deeds. Finally, parental supervision in controlling children towards Islamic educational values.